COLOMBIAN PUBLIC UNIVERSITIES MANAGEMENT INDICATORS ASSESSMENT: A STRUCTURAL EQUATION MODEL APPLICATION - Perez Pulido, Miguel Oswaldo; Orlandoni Merli, Giampaolo; Ramoni Perazzi, Josefa (Innovaciencia, 2014)
In recent years, universities are experimenting new trends that have serious implications for its structure and functioning. The organizations involved in higher education are building strategies to improve university efficiency and ensure their proper functioning. There are several studies regarding university evaluation using indicator systems. The management model of Colombian universities is based on the assessment of the causal relationships between university inputs, measured through a set of indicators that represent the university total capacity. This research presents an analysis of the Colombian public universities performance indicators for the period 2003-2008, which aims to characterize its evolution in time and explore whether it maintains its structure every year. We also investigate whether the indicators proposed by the SUE (State University System) are the best indicators and points out which ones are more reliable. This paper is a descriptive and quantitative study, in which we propose a structural longitudinal model in two waves divided into two time periods (2003-2005) and (2006-2008). We analyzed the percentage changes in several management indicators taking 2003 as the base year. The data were analyzed by the software Lisrel 8.5. Among the most significant results is the positive behavior change for the second period (2006-2008) compared to the first (2003-2005) in the research index.